Scalable decision support for digital preservation - Becker, Christoph (2014)
Preservation environments such as repositories need scalable and context-aware preservation planning and monitoring capabilities to ensure continued accessibility of content over time. This article identifies a number of gaps in the systems and mechanisms currently available and presents a new, innovative architecture for scalable decision-making and control in such environments.